COMPARATIVE ANALYSIS OF ZAKAT MANAGEMENT IN INDONESIA AND KUWAIT - Osman Ali; Maryam Batubara; Febriyani Natari Manik (PT. Radja Intercontinental Publishing, 2024)
Zakat as an Islamic financial instrument has an important role in alleviating poverty. In its management, each country has its own characteristics and differences. As is the management of zakat in Indonesia and Kuwait. This research aims to provide an explanation of zakat management in Kuwait and Indonesia. This research found that there are differences in the management of zakat in the two countries. These differences are reflected in various things. namely, regulations, management institutions, supervisory institutions, models for implementing and collecting zakat, management of collection and distribution.